Attachment-Based Mentalization Profiles of Iranian Children: A Mixed-Method Approach - Masoumeh Zandpour; Majse Lind; Carla Sharp; Jafar Hasani; Farzin Bagheri Sheykhangafshe; Jessica L. Borelli (MDPI AG, 2024)
Mentalization, operationalized as reflective functioning (RF), is the ability to understand one's own and another's mental world implicitly or explicitly. RF is a newly discovered research field in Iran and is largely under-studied in Eastern cultures in general, underscoring the high need for cross-cultural studies in this field of research. A qualitative method was used to examine the ability to understand, process, and respond to high-arousal attachment situations in typical and clinical populations of Iranian children recruited from a Tehran primary school. A well-known semi-structured interview commonly used to assess RF in children was used to collect data. Required information on internalizing and externalizing symptoms, demographic information, and all formal diagnoses of children were collected by parents. The results indicated the identification of four different profiles of RF in children, one of which was adaptive, while the other three were maladaptive. Also, the results showed that typically developing children and those having a high social and economic status (SES) were characterized as having a more adaptive profile of RF, while children from the clinical population and those with a low SES reported a more maladaptive profile (passive mentalizing, helpless mentalizing, narcissistic mentalizing) of RF. The present study is an important step in increasing our understanding of the development of mentalization in children and has significant educational and clinical implications.